Maternal instincts of extensively managed indigenous village chickens - Desta, TT; Wakeyo, O (Journal of the Hellenic Veterinary Medical Society, 2025)
Indigenous village chickens (IVCs) are self-reliant, and they have accumulated traits that assure their survival as a species. The reproductive characteristics and behavioral traits are mainly ascribed to maternal instincts. This study reports the maternal instincts of IVCs gathered using face-to-face interviews with small-scale farmers. Indeed, local hens are excellent mothers. Annually, hens became broody on average four times, and in each cycle, on average, they stayed broody (interrupted laying) for 10 days. In the relatively cold highland region, hens tended to be broody for more days compared to the lowland region (t = 2.563, df = 117, p = 0.012, 95% CI: 0.4505, 3.5128). Squawking and the deterrence of cocks were the most frequently reported signs that have been shown by broody hens. Extended broody is usually discouraged by small-scale farmers by relocating the hen to neighborhoods located out of the reach of the broody hen, hanging it down, and disturbing the hen while it attempts to nest. The dry season was reportedly more suitable for the incubation of eggs and hatching of chicks, for example, the reported average hatchability rate during the dry season was 84%, whereas it was 69% in the wet season. To enhance the rate of hatchability and survival of chicks, it is advisable to match brooding practice with the ideal season and select the right type of hen. Hens with appreciable maternal instincts need to be retained in the family flocks to enhance their reproductive capacity.